Responses of photosynthetic characteristics of oat flag leaf and spike to drought stress - Tian, Haoqi; Zhou, Qingping; Liu, Wenhui; Zhang, Jing; Chen, Youjun; Jia, Zhifeng; Shao, Yuqiao; Wang, Hui (Frontiers in Plant Science, 2022)
Raising crops production via improving photosynthesis has always been focused. Recently excavating and increasing the photosynthetic capacity of non-leaf organs becomes an important approach to crops yield increase. Here we studied the photosynthetic characteristics of the flag leaf and the non-leaf organs including the sheath, the glume and the lemma under greenhouse. The relative water content (RWC), the stomatal characteristics, the photosynthetic pigment contents, the enzyme activities in C3 and C4 pathway and the malate content of the flag leaf and the non-leaf organs on 7, 14, 21, and 28 days after anthesis (denoted by 7DAA, 14DAA, 21DAA, and 28DAA) were determined under well-watered (CK) and water-stressed (D) treatments. Drought stress significantly reduced the RWC of the flag leaf and the non-leaf organs, while the variation of RWC in the glume and the lemma was lower than in the flag leaf. The chlorophyll a content, the chlorophyll b content, the total chlorophyll content and the xanthophyll content in the flag leaf were significantly decreased under D. However, drought stress significantly increased the photosynthetic pigment contents in the glume at the late stage (21DAA and 28DAA). In addition, the induced activities of PEPC, NADP-MDH, NADP-ME, NAD-ME, and PPDK in non-leaf organs under drought stress suggested that the C4 photosynthetic pathway in non-leaf organs compensated the limited C3 photosynthesis in the flag leaf. Non-leaf organs, in particular the glume, showed the crucial function in maintaining the stable photosynthetic performance of oat.